2023
DOI: 10.3390/ijms241310982
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for the Advanced Glycation End Products (RAGE) Pathway in Adipose Tissue Metabolism

Abstract: Advanced glycation end products (AGEs) are mediators in the process of cellular dysfunction in response to hyperglycemia. Numerous data indicate that the accumulation of AGEs in the extracellular matrix plays a key role in the development of obesity-related adipose tissue dysfunction. Through binding of their membrane receptor (RAGE), AGEs affect numerous intracellular pathways and impair adipocyte differentiation, metabolism, and secretory activity. Therefore, inhibiting the production and accumulation of AGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Since then, evidence has accumulated on the major role of the interaction of gHSA with RAGE in the pathogenesis of DM and other diseases [ 46 ]. For example, in obesity, increased levels of AGEs, mainly gHSA, fuel both oxidative stress and the AGE/RAGE axis, which in turn can increase inflammation in already inflammatory tissue, thereby accelerating disease progression [ 47 ]. One of the pathways of kidney damage in DM and the development of diabetic nephropathy is the transdifferentiation of renal tubular cells into myofibroblasts, which occurs when RAGE is activated.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, evidence has accumulated on the major role of the interaction of gHSA with RAGE in the pathogenesis of DM and other diseases [ 46 ]. For example, in obesity, increased levels of AGEs, mainly gHSA, fuel both oxidative stress and the AGE/RAGE axis, which in turn can increase inflammation in already inflammatory tissue, thereby accelerating disease progression [ 47 ]. One of the pathways of kidney damage in DM and the development of diabetic nephropathy is the transdifferentiation of renal tubular cells into myofibroblasts, which occurs when RAGE is activated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the analysis performed after excluding DM patients, BMI values were found to be significantly higher in the resistant HT group. Studies show that an increase in the activity of the AGE-RAGE axis can be both a consequence of obesity and a cause of obesity [37,38]. When assessing the frequency of DM disease, more than half (53.4%) of the patients in the resistant HT group were followed as DM patients, whereas about one out of four patients in the control group were followed as DM patients, representing a significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…The major signaling regulatory pathways of IR include insulinreceptorsubstrate1 (IRS1)/phosphatidylinositol-3-kinase (PI3K)/serine- serine-threoninekinase (Akt) pathway, mitogen-activated proteinkinase (AMPK) pathway, Smad3 pathway, and so on. Recent studies have found that the receptor for advanced glycation end products (RAGE) can reduce insulin sensitivity in tissues critical for glucose metabolism through mediated downregulation of the AMPK downregulation of the Akt signaling pathway, Silencing the signals transmitted by this receptor may be a therapeutic strategy, and the use of RAGE antagonists could potentially improve insulin receptor signaling and enhance insulin sensitivity in patients with impaired glucose tolerance ( 71 ). LKB1 is a serine/threonine kinase, which acts as an upstream kinase of AMPK and can directly phosphorylate AMPK involved in glycolipid metabolism and regulate the onset and progression of IR ( 72 ).…”
Section: Ir Affects Assisted Reproduction Pregnancy Outcomes In Infer...mentioning
confidence: 99%